2022
DOI: 10.1093/biomet/asac070
|View full text |Cite
|
Sign up to set email alerts
|

Splitting strategies for post-selection inference

Abstract: SUMMARY We consider the problem of providing valid inference for a selected parameter in a sparse regression setting. It is well known that classical regression tools can be unreliable in this context due to the bias generated in the selection step. Many approaches have been proposed in recent years to ensure inferential validity. Here, we consider a simple alternative to data splitting based on randomizing the response vector, which allows for higher selection and inferential power than the for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…θ ? Some initial answers to these questions can be found in Neufeld et al (2023) and Rasines & Young (2022).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…θ ? Some initial answers to these questions can be found in Neufeld et al (2023) and Rasines & Young (2022).…”
Section: Discussionmentioning
confidence: 99%
“…Then, U ∼ N n (θ, (1+γ)I n ) and V ∼ N n (θ, (1+γ −1 )I n ) are independent. Rasines & Young (2022) and Leiner et al (2022) applied this decomposition to address Scenario 1 in Section 1. Additionally, Rasines & Young (2022) showed that this leads to asymptotically valid inference under certain regularity conditions, even when X is not normally distributed.…”
Section: Thinning Natural Exponential Families Into Natural Exponenti...mentioning
confidence: 99%
See 3 more Smart Citations